INFLUENCE LEARNING QUALITY LABORATORY PRACTICES AGAINST NURSING LEARNING OUTCOMES PRACTICAL NURSING STUDENT KDM II WIDYA HUSADA SEMARANG - MAULIDTA MAULIDTA (Fakultas Ilmu Keperawatan Universitas Islam Sultan Agung, Semarang, 2017)
Introduction: The laboratory can support in practice the concept of which has been controlled by the students to improve their academic achievement. students will be able to utilize as much as possible if the laboratory facilities of the laboratory is complete and meets the learning needs. Laboratory capable of being a factor supporting the success of the learning process when the tools and lab materials arranged in a systematic manner, besides the things that affect student satisfaction that will affect student learning outcomes is the presence of lecturers competent, learning methods in the laboratory, the division of tasks obviously laboratory workers, and support from managersprogram study. Methods: The study was conducted Observational descriptive analytic observations that a study carried out on a number of variables of the study subjects, the condition is. The samples used as many as 35 students with sampling with random sampling technique Result: the influence of the quality of learning laboratories consisting of reliability, responsiveness, assurance, empathy and practical manifestation of the learning outcomes practical nursing student KDM II Widya Husada Semarang with pvalue> 0.05. Discussion: factors that affect the process and the results of student learning are internal factors and external factors. External factors consist of non-social environment and social environment. The social environment is the relationship of students with faculty, student relationships with employees, while non-social environment includes the natural environment, infrastructure, and the factor of the subject matter. Natural environment such as lighting, and a laboratory atmosphere. Facilities and infrastructure that student learning device that consists of the building, learning tools, facilities, guidebooks, etc.Keywords: quality of teaching, laboratory practice, learning outcomes practicum